PERANAN GONDANG DALAM UPACARA MANGONGKAL HOLI PADA MASYARAKAT BATAK TOBA DI DESA JANJI NATOGU KECAMATAN PAHAE JULU KABUPATEN TAPANULI UTARA - Siregar, Ester Dahlia; Isjoni, Isjoni; Ibrahim, Bedriati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The Mangongkal Holi ceremony is a traditional ceremony carried out from generation to generation by the Toba Batak tribe as a form of respect for the ancestors by digging bones and moving them to a new grave called the monument. The Mangongkal Holi ceremony is always accompanied by a traditional Toba Batak musical instrument, Gondang which plays an important role in the procession of this traditional ceremony. The purpose of this study were 1) To find out the origin of Gondang, 2) To find out the benefits of Gondang for the people of Janji Natogu Village, Pahae Julu Subdistrict, North Tapanuli Regency, 3) To find out the procession form of Gondang when walking the traditional ceremonial process Mangongkal Holi in Janji Natogu Village Pahae Julu Subdistrict, North Tapanuli Regency, 4) To find out the role of Gondang in the traditional ceremony Mangongkal Holi, 5) To find out the efforts made by the community of Janji Natogu Village, Pahae Julu District, North Tapanuli Regency in preserving Gondang musical instruments. Researchers used qualitative research methods with descriptive studies. The results of this study indicate that Gondang's role is very important in the Mangongkal Holi ceremony as the main tool to achieve the relationship between humans and the Creator called Debata Mulajadi Na Bolon in the Toba Batak tribe and as a means of accompanying tor-tor which is till preserved by the community Janji Natogu Village, Pahae Julu District, North Tapanuli Regency.Keywords: Role, Gondang, Ceremony, Mangongkal Holi, Janji Natogu